Pengaruh Motivasi Berprestasi Dan Etos Kerja Terhadap Kinerja Karyawan Pada Hotel Pelita Maumere - Martinus Ie; Walter Obon; Yustina Olivia Da Silva (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
This study aim sto: (1) finding out the description of employees’ performance, works kills, and work experience, (2) analyzing the effect of Work Skills and Work Experience on employees’ performance either partially or simulataneously. The population in thisstuy were employees of Search and Rescue Agency Office Of Maumere as many as 40 people. Due to limited population, research was conducted by cencus or saturated sampling. Data were collected through questionnaires and analyzed using descriptive and inferential statistics methods, namely multiple linear regression. Hyptohesis testing was done through the F test and t test. The result of the descriptive analysis shiwed that the performance variabkes of Employees, Work Skills and Work Experience were categorized as good. The result of the t-test statistic showed that the variables of Work Skills and Work Experience hads a positive and signigiciant eeffect on e’ployees’e performance as partially. The statistical result of the F test showed that simultaneously all independent variables had a significant effect on employees’ performance. The results of the analysis of determination showed that the two independent variables in this study were able to expla in the variation in the performance of the Maumere Search and Rescue Office employeesby 29.7%.